Сучасний стан верхньої межі лісу та приполонинної рослинности - Малиновський, К. (Праці наукового товариства ім. Шевченка, 2003)
Під впливом антропогенних факторів природна верхня межа лісу в Карпатах знижена на 200—300 м по вертикалі і представлена тепер суцільною стіною високостовбурних дерев, нездатних протистояти стихійним явищам. Повідомлено про механізми змін первинних фітоценозів пасторальними, зміни екологічних факторів та про загрозливий стан рідкісних, ендемічних і реліктових видів у смузі контакту лісів з полонинами. As a result of digressive successions caused by anthropogenic factors the upper limit of
forest in the Carpathians has been reduced 200—250 m in altitude. The changes of primary types of vegetation of classes Vaccino-Piceetea, Querco-Fagetea, Betulo-Adenostyletea and Montio-Cardaminetea in the zone of forest contact with alpine meadows are directed towards formation of secondary grass low-productive community, changes in ecological situation and extermination of rare, relict and endemic species. The renewal of forest limit is possible by means of protection, separation of forestry and pasture management and reafforestation.